Analisis Pemahaman Konseptual dan Prosedural Siswa dalam Menyelesaikan Soal Matematika Berdasarkan Gaya Belajar - Wawan; Ahmad Talib; Nurwati Djam’an (Issues in Mathematics Education (IMED), 2017)
This Research aimed to obtain information about the analysis of student’s conceptual and procedural comprehending in solving mathematics problems based on learning styles, the aimed of this research was done by descriptive qualitative research. The subject of this research consists of six people. The six subjects were chosen based on the learning style category of students of class X in SMA Bulukumba. Two subjects represented visual learning style categories (PAR and MRK), two subjects represented auditory learning styles categories (ARR and HMY) and two subjects represented kinesthetic learning styles categories (MTA and SZD). Instruments in this research were the researchers itself as the main instrument supported by the instrument of learning style questionnaire, conceptual and procedural comprehending test and interview guidelines. The results of this research indicate that subjects with visual learning styles and subjects with auditory learning styles meet three indicators of conceptual comprehending. Whereas the subject with kinesthetic learning styles is the subject of MTA meet three indicators of conceptual comprehending and the subject of SZD meet only two indicators of conceptual comprehending. For procedural comprehending all subjects do not meet the knowledge indicators of the algorithm, knowledge of techniques and methods and criteria for determining when to use appropriate procedures. This suggests that the learning style of the students has no connection with their conceptual and procedural comprehending